Revisiting Kahrudin Yunus On Bersamaism: A Natural Law Design For Indonesia Today - Rahmat, Aulia (Prophetic Law Review, 2021)
"At the beginning of the independence era, Kahrudin Yunus proposed a natural law-based economic law model, but it declined in recent years or discussion in scholarly communities. This article examines the trend toward relations between state, government, and the rule of economic law based on bersamaism. Interpretive analytic is the method employed. Bersamaism’s basic assumptions are based on the universality of Quran truth, and the state must be positioned as an intermediary in legal and economic activities. Bersamaism is similar to the natural law school in terms of thought, but it also provides an understanding empirical considerations, actually has provided a prototype for the development of an economic system for Indonesia."Keywords: Economic justice; natural law; prophetic lawMenilik Kahrudin Yunus Mengenai Bersamaisme: Desain Hukum Alam Untuk Indonesia Hari IniAbstrakPada awal era kemerdekaan, Kahrudin Yunus mengajukan model hukum ekonomi berbasis hukum alam, namun beberapa tahun belakangan ini ditolak dalam diskusi di kalangan cendikiawan. Artikel ini mengkaji kecenderungan hubungan antara negara, pemerintah, dan supremasi hukum ekonomi berbasis Bersamaisme. Analitik interpretatif adalah metode yang digunakan. Asumsi dasar Bersamaisme didasarkan pada universalitas kebenaran Alquran, dan negara harus diposisikan sebagai perantara dalam kegiatan hukum dan ekonomi. Bersamaisme mirip dengan mazhab hukum alam dalam hal pemikiran, tetapi juga memberikan pemahaman pertimbangan empiris, sebenarnya telah memberikan prototipe bagi pengembangan sistem ekonomi bagi Indonesia.Kata kunci: Keadilan ekonomi; hukum alam; hukum profetik